- #1

dtchannell88

- 4

- 0

Equations i thought might be useful..:

E=I*((r*L/2) + R)

My attempt:

Since..

I =emf/2rL+R

emf=I*((r*L/2) + R)

Then the force is equal to length, by current, by magnetic field. Because the current is going in the same direction in the two wires it will be an attraction force.

When you get Force as a function of L,

F = (µ0 *E^2)/(2*pi*a*r^2*L) where

µ0=permeability

pi = 3.141592...

Im unsure if this is even right, and where I go from here.. all help is appreciated..